Weana Tanz (Wiener Tänze) Teil 1: Geschichte und Typologie - Deutsch, Walter (2010)
The "Weana Tanz" (Viennese dance music) are instrumental plays of music, the character of which developped out of the alpine "landler melodics. They were shaped to a specific genre of urban folk music by the Viennese "Tanzgeigern". In the history of Viennese music the WEANA TANZ represents an important period. Their discription and interpretation in 8 chapters show the extraordinary position they held in the music life of the 19th century. Manuscripts and prints of the early 19th and 20th century are documents of the historical period of development, its expression in style and melody as well as their musical function for entertainment and social gatherings. As an addition sound recordings are selected from the first productions of records between 1900 and 1930. One chapter is dedicated to remarkable composers and exponents. In their lives and opus we find the seasonable situation of music life in Vienna. A detailed register gives access to the exceptionally abundant content of this volume. After this monography the "WEANA TANZ" as part 1 of the 20th volume of the Encyclopaedia CORPUS MUSICAE POPULARIS AUSTRIACAE follows volume 2 with a collection of 130 "Viennese dances" which can be interpreted in diverse instrumentations.